(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the contribution of social support and meaning in life to the psychological well-being of working elderly. The increasing number of elderly who continue to work in Indonesia is an interesting phenomenon to study because it is related to the condition of psychological well-being in old age. This study used a quantitative approach with a multiple linear regression method. The research subjects were 92 working elderly selected using quota sampling technique. Data were collected through a scale of social support, meaning in life, and psychological well-being, then analyzed simultaneously and partially. The results showed that social support and meaning in life simultaneously contributed significantly to psychological well-being in working elderly with a significance value of 0.000 < 0.05. Partially, social support had a significant contribution to psychological well-being with a calculated t value of 7.770 > t table 1.987 and a significance of 0.000 < 0.05. In contrast, the meaning in life did not show a significant contribution to psychological well-being with a calculated t value of -0.026 < t table 1.987 and a significance of 0.979 > 0.05. These findings indicate that social support is an important factor in improving psychological well-being in working elderly people.